Evaluating the Kikuhime pressure monitor for use with sports compression clothing - Brophy-Williams, N.; Driller, M. W.; Halson, S. L.; Fell, J. W.; Shing, C. M. (Sports Engineering, 2014)
Reporting accurate and reliable measures of pressure exerted by sport compression clothing assists in the interpretation and comparison of study findings. The objective of the current study was to assess the validity and reliability of the Kikuhime pressure monitoring device to measure the pressure of sport compression garments. To assess validity, three separate Kikuhime sensors were compared to known pressures inside a water column, at 5 mmHg increments ranging from 5 to 100 mmHg. Intra- and inter-tester reliability was determined by comparing the results of two individuals performing five interface pressure measures at six different landmarks across the lower and upper leg of an athlete wearing sports compression leggings. All three sensors tested exhibited a very high intra-class correlation with the reference value (mean ICC = 0.996). The typical error of measurement was low for both intra- and inter-tester reliability (mean ± SD: 1.3 ± 0.9 and 1.8 ± 0.9 mmHg, respectively). These results expressed as a coefficient of variation were 4.9 ± 2.4 and 7.4 ± 5.4 %, respectively. The findings from the current study suggest that the Kikuhime device is a valid and reliable instrument for use in situ when measuring the pressure of sports compression garments in athletes assuming a static standing posture. The instrument could be used in future research involving compression garments to accurately quantify interface pressures and their subsequent effect on physiological and/or performance measures.